2002
DOI: 10.1024/0300-9831.72.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Carotenoid and Vitamin E Concentrations in Women Living in a Rural West African (Gambian) Community

Abstract: Vitamin E and carotenoid pigments are important nutrients for the maintenance of health and protection of tissues against free radical damage. They also play a potential role in disease-risk-prediction and -protection, but little is known about their physiological and sociodemographic correlates and determinants, especially in a West African context. As part of a study of reproductive health in rural Gambian women, blood samples were obtained from 1286 women aged 15 to 54 years, living in the Farafenni area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…(41) Finally, being pregnant was associated with a lower gamma-tocopherol:alphatocopherol ratio because pregnant girls had lower gammatocopherol concentrations than their non-pregnant peers, a finding that is in accord with the study in Gambia. (20) The plasma concentration of alpha-tocopherol found in this study (mean 13⋅52 μmol/l, median 13⋅05 μmol/l) was lower than that typical for high-income settings (11) but was roughly similar to reports from neighbouring countries. In previous studies, 10-to 19-year-old girls in Malawi had a mean serum concentration of alpha-tocopherol of 10⋅2 μmol/l, (14) 5-to 10-year-old children in Tanzania had a median of 15⋅4 μmol/l, (16) and pregnant women in Tanzania had a mean of 15⋅4 μmol/l.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…(41) Finally, being pregnant was associated with a lower gamma-tocopherol:alphatocopherol ratio because pregnant girls had lower gammatocopherol concentrations than their non-pregnant peers, a finding that is in accord with the study in Gambia. (20) The plasma concentration of alpha-tocopherol found in this study (mean 13⋅52 μmol/l, median 13⋅05 μmol/l) was lower than that typical for high-income settings (11) but was roughly similar to reports from neighbouring countries. In previous studies, 10-to 19-year-old girls in Malawi had a mean serum concentration of alpha-tocopherol of 10⋅2 μmol/l, (14) 5-to 10-year-old children in Tanzania had a median of 15⋅4 μmol/l, (16) and pregnant women in Tanzania had a mean of 15⋅4 μmol/l.…”
Section: Discussionsupporting
confidence: 78%
“…(10,11) Studies in Sub-Saharan African countries have reported mean/median plasma/ serum concentrations from 9⋅4 to 16⋅1 μmol/l for infants, children, and adolescents, (12)(13)(14)(15)(16)(17) from 4⋅8 to 19⋅1 μmol/l for non-pregnant adults and elderly, (15,(18)(19)(20)(21)(22)(23) and from 11⋅0 to 25⋅5 μmol/l for women who were pregnant or up to 2 weeks post-partum. (17,20,(24)(25)(26)(27) Alpha-tocopherol is transported in the blood in lipoproteins and since blood cholesterol levels vary in different populations and age groups, the alpha-tocopherol:total cholesterol ratio is also of interest as an indicator of alpha-tocopherol status. On the other hand, lipoproteins may be low in cases of proteinenergy undernutrition; therefore, undernutrition may mask vitamin E deficiency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These workers also showed that the enzyme was down-regulated by retinoic acid and that regulation was restricted to β-carotene15, 15 dioxygenase activity in the duodenum. There is also some indirect evidence from studies in The Gambia 9 that the enzyme targets β-carotene in preference to α-carotene and enzyme studies also confirm this. 10 Interpreting plasma concentrations of carotenoids There are no generally accepted criteria of adequacy with which to assess 'carotenoid status'.…”
Section: Factors Influencing Activity Of Gut β-Carotene 1515 -Dioxygmentioning
confidence: 68%